PEMANFAATAN BUSINESS INTELLIGENCE UNTUK MONITORING TREN PENYAKIT DI RUMAH SAKIT - Supriono, Agus; Herwanto (Universitas Siber Indonesia, 2024)
In the digital transformation era, hospitals are increasingly aware of using information technology, mainly through the Hospital Information System (HIS), to enhance efficiency, service quality, and data-driven decision-making. The primary focus on developing Business Intelligence (BI) enables hospitals to gain profound insights from data, especially regarding the quantity and distribution of diseases in the service area. This research discusses the urgency of leveraging BI to improve disease management, prevention, and evidence-based policies. In addressing the complexity of risk management in healthcare services, BI supports the design of prevention strategies, efficient resource allocation, and responses to public health needs. The research method focuses on BI development using SIM RS data related to the quantity and distribution of diseases. Key BI components, such as Data Warehouse, Business Analytics, Data Mining, and Business Performance Management, are utilized to achieve research objectives. The Extract, Transform, Load (ETL) process forms the foundation for optimizing the transformation of operational data into meaningful information. The research results indicate that implementing BI, mainly through the Power BI platform, clearly visualizes patient characteristics, demographics, and disease distribution. Management can make better decisions, improve service efficiency, and enhance patient experience. This study contributes to understanding the importance of utilizing HIS data through BI to enhance healthcare service quality and support strategic hospital decision-making.